2004
DOI: 10.1080/10473289.2004.10470925
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of PCDD/Fs, PCBs, Chlorobenzenes, Chlorophenols, and PAHs from Polyvinylchloride Combustion at Various Temperatures

Abstract: The effect of temperature on polyvinylchloride (PVC) combustion using a downstream tubular furnace was investigated for the formation of polycylcic aromatic hydrocarbons (PAHs) and chlorinated compounds. As the temperature increased, higher levels of PAHs were generated. Chlorinated compounds reached a peak at 600°C, with low emissions recorded at 300 and 900°C. There was a close correlation (R 2 ϭ 0.97) among polychlorinated biphenyls (PCBs), hexachlorobenzene, pentachlorobenzene, and polychlorinated dibenzo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
(23 reference statements)
3
25
0
Order By: Relevance
“…Kim et al [13] also found an increase of the 16 main PAH yields with temperature during combustion of 0.5 g PVC with 2 L/min air in a downstream vertical tubular furnace at temperatures of 300, 600 and 900 8C: about 800, 3500 and 5000 ppm, respectively. In that work, the high yield for phenanthrene (1400 ppm maximum), higher than that of naphthalene (1100 ppm maximum), was remarkable.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 4 more Smart Citations
“…Kim et al [13] also found an increase of the 16 main PAH yields with temperature during combustion of 0.5 g PVC with 2 L/min air in a downstream vertical tubular furnace at temperatures of 300, 600 and 900 8C: about 800, 3500 and 5000 ppm, respectively. In that work, the high yield for phenanthrene (1400 ppm maximum), higher than that of naphthalene (1100 ppm maximum), was remarkable.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Results obtained are sometimes difficult to compare because of the variety of operating conditions and systems used. But there is not much research on concurrent emission analysis of PAHs, ClBzs, ClPhs and PCDD/Fs from the pyrolysis and combustion of PVC at different temperatures [13]. The aim of this work is to provide a comprehensive laboratory study of the pyrolysis and combustion products of pure PVC at different temperatures, mainly focusing on a detailed analysis of the great amount of PAHs generated by pyrosynthesis reactions and the chlorine aromatic compounds evolved.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 3 more Smart Citations